Архівні документи як джерело з вивчення діяльності Київського товариства охорони пам’яток старовини й мистецтва - Качковська, Леся Ростиславівна; Kachkovska, Lesya R. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто зміст архівних документів з ЦДІА у м. Київ. The the article deals with archival documents taken from the Central State Historical Archive of Ukraine in Kiyv that describe the activity of Kyiv Society for the Protection of the Artifacts of Antiquities. the researcher focuses attention on the paper work activity of the society that deals with the presentation and preservation of the cultural heriyage on of the Pravoberezhna Ukrayina.
The Archived Documents as Source of the Study of Kyiv Society for the Protection of the Artifacts of Antiquities and Arts
Keywords: Архівні документи; культурна спадщина; пам'ятка; Kyiv Society for the Protection of the Artifacts of Antiquities; cultural heritage; archival documents